(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The southern Levant—historically referred to as Canaan, the Land of Israel, Judea, and Palestine—has functioned as a nexus of civilizations for over 5,000 years. This forensic historiography integrates archaeological artifacts, ancient inscriptions, genetic analyses, demographic records, and contemporary chronicles to investigate the interconnected histories of Jewish, Arab (including Palestinian), and other Levantine populations. It prioritizes empirical evidence while acknowledging interpretive challenges, highlighting themes of continuity, conquest, assimilation, and conflict. Genetic and archaeological data suggest substantial ancestral overlap among Levantine groups from the Bronze Age, with modern Lebanese populations exhibiting particularly high continuity with ancient Canaanites. Ottoman-era demographics reveal a predominantly Arab Muslim and Christian population in Palestine, with gradual Jewish increases through immigration in the 19th century. Though modern national identities formed amid 19th- and 20th-century nationalism, colonialism, and geopolitical shifts, this study posits that the Israel-Palestine conflict derives primarily from 20th-century developments rather than ancient animosities, while emphasizing the need for balanced scholarly inquiry.